Consensus statement on the management of urticaria - Kiran V Godse; Vijay Zawar; D S Krupashankar; Mukesh Girdhar; Sanjiv Kandhari; Sandipan Dhar; Sanjay Ghosh; Murlidhar Rajagopalan; Torsten Zuberbier (Wolters Kluwer Medknow Publications, 2011)
This consensus statement was developed by Special Interest Group - Urticaria (IADVL). Urticaria, a heterogeneous group of diseases, often cannot be recognized by its morphology. Due to non-specific and non-affordable diagnosis, management of urticaria, especially chronic urticaria, is very challenging. This guideline includes definition, causes, classification and management of urticaria. Urticaria has a profound impact on the quality of life and causes immense distress to patients, necessitating effective treatment. One approach to manage urticaria is identification and elimination of the underlying cause(s) and/or eliciting trigger(s), while the second one is treatment aimed at providing symptomatic relief. This guideline recommends use of second-generation non-sedating H1 antihistamines as the first-line treatment. The dose can be increased up to four times to meet the expected results. In case patients still do not respond, appropriate treatment options can be selected depending on the cost.